Platelet-derived microparticles provoke chronic lymphocytic leukemia malignancy through metabolic reprogramming - Gharib, Ehsan; Veilleux, Vanessa; Boudreau, Luc H.; Pichaud, Nicolas; Robichaud, Gilles A. (Frontiers in Immunology, 2023)
It is well established that inflammation and platelets promote multiple processes of cancer malignancy. Recently, platelets have received attention for their role in carcinogenesis through the production of microvesicles or platelet-derived microparticles (PMPs), which transfer their biological content to cancer cells. We have previously characterized a new subpopulation of these microparticles (termed mito-microparticles), which package functional mitochondria. The potential of mitochondria transfer to cancer cells is particularly impactful as many aspects of mitochondrial biology (i.e., cell growth, apoptosis inhibition, and drug resistance) coincide with cancer hallmarks and disease progression. These metabolic aspects are particularly notable in chronic lymphocytic leukemia (CLL), which is characterized by a relentless accumulation of proliferating, immunologically dysfunctional, mature B-lymphocytes that fail to undergo apoptosis. The present study aimed to investigate the role of PMPs on CLL metabolic plasticity leading to cancer cell phenotypic changes. CLL cell models were therefore co-incubated with human PMPs, which resulted in increases in cellular oxygen consumption rates, ATP levels, and ROS production. Upon the evaluation of cancer cellular processes, we observed that PMP co-cultures with cells significantly increased CLL proliferation rates and invasion capacity. Using bioinformatics tools, we also characterized specific pathways and essential genes involved in PMP-mediated metabolic-reprogramming through the examination of patient cohorts with early and advanced CLL stages. These metabolic gene expression signatures were then validated in platelet-derived mitochondria-recipient CLLs. Lastly, PMP-induced metabolic reprogramming of CLL cells also demonstrated increased cell chemoresistance to commonly used therapeutics, Cytarabine, Venetoclax, and Plumbagin. Altogether, these findings depict a new platelet-mediated pathway of cancer pathogenesis. We also highlight the impact of PMPs in CLL metabolic reprogramming and disease progression.